Chemical Enhancement vs Molecule-Substrate Geometry in Plasmon-Enhanced Spectroscopy - Rodriguez, Raul D.; Villagomez, Carlos J.; Khodadadi, Amirhassan; Kupfer, Stephan; Averkiev, Andrey; Dedelaite, Lina; Tang, Feng; Khaywah, Mohammad Y.; Kolchuzhin, Vladimir; Ramanavicius, Arunas; Adam, Pierre-Michel; Gräfe, Stefanie; et al. (ACS Photonics, 2021)
Light interaction with metal nanostructures exposes exciting phenomena such as strong amplification and localization of electromagnetic fields. In surface-enhanced Raman spectroscopy (SERS), the strong signal amplification is attributed to two fundamental mechanisms, electromagnetic and chemical enhancement (EM and CM, respectively). While the EM mechanism is accepted as the main responsible for signal amplification, a long-standing controversy on the CM mechanism's role still prevails. The CM contribution can be evidenced when compared to the nonenhanced (or bulk) Raman signal as a change in intensity ratios, peak shifts, or appearance of new Raman modes. However, it is also possible to induce similar spectral variations by changing the relative orientation between the electric field and molecule or when a high electric field gradient is achieved. Therefore, in this work, we show specific spectral changes in SERS affected by the molecular orientation, while changes in other modes can be attributed to chemical enhancement. On the basis of our experimental and quantum chemical results for cobalt phthalocyanine, we identify low-frequency Raman modes (LFMs) sensitive to charge-transfer compared to high-frequency modes (HFMs) that are rather sensitive to geometrical effects and temperature changes. These results provide new evidence on the role of molecule excitation/polarization that comes now as a more general and dominant effect than the chemical enhancement mechanism so far attributed to charge-transfer processes. These findings make it possible to engineer multifunctional Raman molecular probes with selective sensitivity to the local environment (HFMs) and charge-transfer processes (LFMs).
CRIS-Team Scopus Importer:2023-04-20
Keywords: nanospectroscopy; phthalocyanines; plasmonics; quantum chemistry; SERS; spectral artifacts; surface-enhanced Raman spectroscopy